Global Trends and Hotspots in the Association between Chronic Kidney Disease and Cardiovascular Diseases: A Bibliometric Analysis from 2010 to 2023 - Binghao Chen; Xiangqiu Wang; Dikang Pan; Jingyu Wang (Cardiorenal Medicine)
Introduction: This study endeavors to evaluate the distribution patterns and research frontiers within the international literature on the association between chronic kidney disease and cardiovascular diseases in the medical field, through bibliometric analysis and visualized information. Methods: The Web of Science Core Collection database was selected as the data source from 2010 to 2023, and articles related to the association between chronic kidney disease and cardiovascular diseases were retrieved. The article data were analyzed through CiteSpace for bibliometric mapping, involving the examination of keywords, references, country/region distributions, and institutional contributions to identify and understand the evolving research dynamics and frontiers in this interdisciplinary field. Results: A total of 2,936 publications on the association between chronic kidney disease and cardiovascular diseases were included. The country with the most publications was USA (n = 904), and the institution with the most publications was University of Pennsylvania (n = 116). The most frequent keywords were chronic kidney disease (n = 2,194), cardiovascular disease (n = 1,188), and mortality (n = 604). The top 20 keywords and top 10 references that burst during 2010 to 2023 were listed. Conclusion: The association between chronic kidney disease and cardiovascular diseases has sparked extensive research, particularly in high-prevalence areas. From 2010 to 2023, publications on the association between chronic kidney disease and cardiovascular diseases show a linear increase. Current research hotspots and frontiers are mainly in cardiovascular-kidney-metabolic syndrome; innovative therapies and drug impact; gut microbiome; Mendelian randomization analysis. Overall, our study offers a comprehensive scientometric analysis of the association between chronic kidney disease and cardiovascular diseases, providing valuable insights for both researchers and healthcare professionals in the field.